Intrinsic stresses in DLC coatings deposited in modes of DC and pulse bias potentials - Kalinichenko, A.I.; Perepelkin, S.S.; Strel’nitskij, V.E. (Вопросы атомной науки и техники, 2015)
Formula for intrinsic stress calculation in coatings deposited from ion flux in the pulse potential mode is derived. The criterion of applicability of derived formula is proposed which permits determining critical parameters of the pulse potential mode. Calculation of stress in DLC coatings at deposition of low-energy ions C+ from filtered vacuum arc plasma is presented. The qualitative agreement of calculated stresses with experimental data is stated. The important role of deposition temperature for intrinsic stress control in deposited coating is noted.